Risk factors for microcystic macular oedema in glaucoma. Issue 4 (5th November 2021) - Mahmoudinezhad, Golnoush; Salazar, Diana; Morales, Esteban; Tran, Peter; Lee, Janet; Hubschman, Jean-Pierre; Nouri-Mahdavi, Kouros; Caprioli, Joseph
Abstract : Background/aims: To identify clinical characteristics and factors associated with microcystic macular edema (MME) in patients with primary open-angle glaucoma (POAG). Methods: We included 315 POAG eyes between 2010 and 2019 with good-quality macular volume scans that had reliable visual fields (VF) available within 6 months in this observational retrospective cohort study. Eyes with retinal pathologies except for epiretinal membrane (ERM) were excluded. The inner nuclear layer was qualitatively assessed for the presence of MME. Global mean deviation (MD) and Visual Field Index (VFI) decay rates, superior and inferior MD rates and pointwise total deviation rates of change were estimated with linear regression. Logistic regression was performed to identify baseline factors associated with the presence of MME and to determine whether MME is associated with progressive VF loss. Results: 25 out of 315 eyes (7.9%) demonstrated MME. The average (±SD) age and MD in eyes with and without MME was 57.2 (±8.7) versus 62.0 (±9.9) years (p=0.02) and −9.8 (±5.7) versus −4.9 (±5.3) dB (p<0.001), respectively. Worse global MD at baseline (p=0.001) and younger age (p=0.02) were associated with presence of MME. ERM was not associated with the presence of MME (p=0.84) in this cohort. MME was not associated with MD and VFI decay rates (p>0.49). Conclusions: More severe glaucoma and younger age were associated with MME. MME was not associated with faster global VF decay in this cohort. MME may confound monitoring of glaucoma with full macular thickness.